1999
DOI: 10.1111/j.1949-8594.1999.tb17475.x
|View full text |Cite
|
Sign up to set email alerts
|

A Locally Based Science Mentorship Program For High Achieving Students: Unearthing Issues That Influence Affective Outcomes

Abstract: Little is known about the impact of university-situated science mentoring programs on the affect of high achieving high school students, and few science mentorship programs have been described. This study describes a university-based summer science mentorship program designed to offer participants a challenging science research experience and identifies issues that influence the affective outcomes for participants. Interview data was collected from eight participants at the 2nd and 6th weeks of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Mentors were responsible for guiding the apprentices' acquisition of background knowledge, establishing the research framework for the apprenticeship projects, and providing day-to-day guidance and troubleshooting. Other studies on university apprenticeship experiences for high school students suggest that faculty mentors also affect the manner in which students learned about and discussed science (Bleicher, 1996;Templin, Engemann, & Doran, 1999). Given the seminal role they play in the apprenticeship experience, postapprenticeship interviews with the mentors were used to ascertain their perceptions of what the apprentices learned from their apprenticeships, as well as their own views of the nature of science and science inquiry.…”
Section: Mentorsmentioning
confidence: 99%
“…Mentors were responsible for guiding the apprentices' acquisition of background knowledge, establishing the research framework for the apprenticeship projects, and providing day-to-day guidance and troubleshooting. Other studies on university apprenticeship experiences for high school students suggest that faculty mentors also affect the manner in which students learned about and discussed science (Bleicher, 1996;Templin, Engemann, & Doran, 1999). Given the seminal role they play in the apprenticeship experience, postapprenticeship interviews with the mentors were used to ascertain their perceptions of what the apprentices learned from their apprenticeships, as well as their own views of the nature of science and science inquiry.…”
Section: Mentorsmentioning
confidence: 99%
“…In some ways, students' feelings toward Dr C very much reflect students' feelings toward real scientists. For example, Templin, Doran and Engemann's (1999) research on mentoring by human scientists found that students who claimed regular contact with their mentors reported program satisfaction, while those with a weaker relationship reported negative feelings about the program (p. 208). In the present study, students who used Dr C the most reported in the interviews that they felt the most positively about him, feeling he was useful and helped them learn.…”
Section: Discussionmentioning
confidence: 99%
“…A review of multiple studies examining research apprenticeships found that the successes of apprenticeship type programs and environments are tied to the direct interaction of students with scientists in authentic scientific settings (Sadler et al, 2010). Some of the studies with high school students (Stake and Mares, 2005;Templin et al, 1999) reviewed in this paper yielded data indicating increased confidence and self-efficacy in "doing science" after participation in a science apprenticeship program (Sadler et al, 2010).…”
Section: Introductionmentioning
confidence: 91%